2022
DOI: 10.1111/bju.15893
|View full text |Cite
|
Sign up to set email alerts
|

Re‐challenging chemotherapy after pembrolizumab in platinum‐refractory urothelial carcinoma

Abstract: To assess the real-world clinical benefit of re-challenging chemotherapy after pembrolizumab in patients with metastatic urothelial carcinoma (mUC), as there have been several reports suggesting that programmed cell death protein-1/ programmed death-ligand 1inhibitors can restore platinum sensitivity. Patients and MethodsOf 236 patients treated with pembrolizumab, we excluded 45 patients who did not experience progressive disease (PD) for pembrolizumab during the follow-up and 86 patients who discontinued pemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Platinum rechallenge has been reported to be a potentially effective treatment for advanced UC 13–20 . For example, Gravis et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Platinum rechallenge has been reported to be a potentially effective treatment for advanced UC 13–20 . For example, Gravis et al.…”
Section: Discussionmentioning
confidence: 99%
“…Platinum rechallenge has been reported to be a potentially effective treatment for advanced UC. [13][14][15][16][17][18][19][20] For example, Gravis et al reported unexpected responses to cisplatin rechallenge after ICIs in metastatic UC, which was refractory to platinum regimens. 13 They reported that 2 of 14 patients achieved partial responses and 10 of 14 achieved stable disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protocols for discontinuing pembrolizumab treatment and administering palliative radiation were not standardized among the institutes. Third-line treatment including chemotherapy could impact the prognosis [27] , [28] . However, we could not incorporate this concept in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Immune CPIs for mUC patients were approved by the FDA in 2017, 1 leading to a dramatic change in the treatment landscape. However, the majority of patients did not respond to CPIs 2 . In short, the results from the KEYNOTE‐045 trial after more than 2 years of follow‐up exhibited only a modest improvement in progression‐free survival rate (2.1 months, 95% CI: 2.0–2.2 months), ORR (21.1%, 95% CI: 16.4%–26.5%) and disease control rate (DCR: 38.5%, 95% CI: 32.7%–44.6%) in the CPI arm compared with those in the conventional chemotherapy arm 3 .…”
Section: Introductionmentioning
confidence: 99%